Cultivation Strategy for Freshwater Macro- and Micro-Algae as Biomass Stock for Lipid Production - Marieska Verawaty; Elda Melwita; Putri Apsari; Mayumi Mayumi (Journal of Engineering and Technological Sciences, 2017)
In this research, an algae cultivation strategy was studied. Integrating algae cultivation with wastewater treatment is currently seen as one of the most economical ways of producing algae biomass. A combination of an anaerobic baffled reactor (ABR) and a constructed wetland (CW) was applied for treating domestic wastewater with an additional collection tank for improving effluent quality. The effluent produced from the three stages was used as algae cultivation media and suplemented with 10% bold basal medium (BBM). The results showed both micro- and macro-algae growth and their lipid contents were higher when they were grown in effluent-BBM (9:1 v/v) media. The lipid content of the micro-algae mixed culture was 16.5% while for macro-algae Oedogonium sp and Cladophora sp it was 6.90% and 6.75% respectively.